1982
DOI: 10.1177/00220345820610100901
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Whole Mouth Resting and Stimulated Salivary Measurement Procedures

Abstract: Methods for collection and stimulation of whole mouth saliva were compared. Resting salivary flow values were roughly equivalent for draining, spitting, suction, and swab collection techniques, but the swab technique was less reliable. Gustatory and masticatory stimuli induced significantly higher salivary flow compared to resting levels, but the between- and within-subject variances were also higher. Stimulation produced a fairly constant addition of saliva whether individual resting flow levels were low or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
280
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(306 citation statements)
references
References 11 publications
4
280
3
6
Order By: Relevance
“…Participants were refrained from eating, drinking, or smoking for at least 2 hours before the test (Navazesh and Christensen, 1982;Navazesh, 1993).…”
Section: Blood and Saliva Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were refrained from eating, drinking, or smoking for at least 2 hours before the test (Navazesh and Christensen, 1982;Navazesh, 1993).…”
Section: Blood and Saliva Samplingmentioning
confidence: 99%
“…Several studies have shown that this marker and others are present in saliva. Thus, its use as a diagnostic fluid could have many advantages comparing to serum: saliva collection is noninvasive, simple, can be collected repeatedly without discomfort of patients and could be a reliable way to detect tumor markers and thus contribute to monitoring the effectiveness of chemotherapy (Navazesh and Christensen, 1982;Streckfus and Bigler, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Objective measures of saliva quantity and quality are obtained through salivary stimulation 22 and different methods are used to stimulate salivary secretion, including the chewing of gum, paraffin wax, rubber strips, and citric acid. 35 There is evidence that a very low salivary flow significantly increases the risk of developing dental caries 36 , which underscores the importance of the recognition of reduced salivary flow by dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Unstimulated whole saliva was collected through the spit method, as described by Navazesh and Christensen (19). The unstimulated saliva flow was expressed in mL per 5 min.…”
Section: Oral Examinationsmentioning
confidence: 99%